2005
DOI: 10.1523/jneurosci.3420-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Dissociation of Encoding and Retrieval Processes in the Human Hippocampus

Abstract: The hippocampal formation performs two related but distinct memory functions: encoding of novel information and retrieval of episodes. Little evidence, however, resolves how these two processes are implemented within the same anatomical structure. Here we use high-resolution functional magnetic resonance imaging to show that distinct subregions of the hippocampus are differentially involved in encoding and retrieval. We found that regions early in the hippocampal circuit (dentate gyrus and CA fields 2 and 3) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
222
4
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(263 citation statements)
references
References 38 publications
35
222
4
2
Order By: Relevance
“…One set of studies finds that the hippocampus subserves recollection, but not familiarity, of memoranda such as words or pictures (Eldridge et al 2000(Eldridge et al , 2005Weis et al 2004;Wheeler and Buckner 2004;Yonelinas et al 2005;Montaldi et al 2006;Diana et al 2007Diana et al , 2010Cohn et al 2009;Ford et al 2010;Rugg et al 2012;Yu et al 2012). More specifically, the hippocampus has been found to respond more strongly to words or pictures reported as "remembered" (Eldridge et al 2000(Eldridge et al , 2005Wheeler and Buckner 2004;Yonelinas et al 2005;Montaldi et al 2006), in correct versus incorrect retrieval of the encoding context (Weis et al 2004;Tendolkar et al 2008;Duarte et al 2011;see Staresina et al 2012b for a related intracranial electroencephalography [iEEG] study), and in associative relative to nonassociative recognition (Kirwan and Stark 2004) or recognition of compound words (Ford et al 2010). Recent studies propose that hippocampal activity is not related to the subjective sense of recollection, but modulated by the amount of contextual information actually retrieved Yu et al 2012).…”
Section: Hippocampus and Mtlmentioning
confidence: 99%
See 1 more Smart Citation
“…One set of studies finds that the hippocampus subserves recollection, but not familiarity, of memoranda such as words or pictures (Eldridge et al 2000(Eldridge et al , 2005Weis et al 2004;Wheeler and Buckner 2004;Yonelinas et al 2005;Montaldi et al 2006;Diana et al 2007Diana et al , 2010Cohn et al 2009;Ford et al 2010;Rugg et al 2012;Yu et al 2012). More specifically, the hippocampus has been found to respond more strongly to words or pictures reported as "remembered" (Eldridge et al 2000(Eldridge et al , 2005Wheeler and Buckner 2004;Yonelinas et al 2005;Montaldi et al 2006), in correct versus incorrect retrieval of the encoding context (Weis et al 2004;Tendolkar et al 2008;Duarte et al 2011;see Staresina et al 2012b for a related intracranial electroencephalography [iEEG] study), and in associative relative to nonassociative recognition (Kirwan and Stark 2004) or recognition of compound words (Ford et al 2010). Recent studies propose that hippocampal activity is not related to the subjective sense of recollection, but modulated by the amount of contextual information actually retrieved Yu et al 2012).…”
Section: Hippocampus and Mtlmentioning
confidence: 99%
“…High-resolution fMRI (Carr et al 2010) enables an alternate distinction, between the different hippocampal subfields. The few studies available at the time of writing seem to reveal a dissociation between encoding processes observed in DG/CA3 and retrieval (or recollection) in CA1/subiculum (Zeineh et al 2003;Eldridge et al 2005;Viskontas et al 2009). ferior parietal lobule, lateral temporal cortex, and MTL, has been identified as preferentially active in situations in which external stimuli are absent.…”
Section: Hippocampus and Mtlmentioning
confidence: 99%
“…Among event-related fMRI studies employing separate study and test phases, it has occasionally been reported that correctly-recognized (old) items elicit greater hippocampal activity than correctly-rejected (new) items (e.g., Donaldson et al, 2001;Stark & Squire, 2001). More frequently, enhanced hippocampal activity has been reported for recognition test items that are accompanied by either "remember" or accurate source memory judgments, relative to when items are designated with "know" responses or lack source information (e.g., Cansino et al, 2002;Eldridge et al, 2000;Johnson & Rugg, 2007;Wheeler & Buckner, 2004;Woodruff et al, 2005;Yonelinas et al, 2005 to imply that enhanced hippocampal activity is associated with the retrieval (recollection) of qualitative information about a study episode, rather than an acontextual sense of familiarity (Rugg & Yonelinas, 2003; but see Squire et al, 2007). Of significance, however, is that other fMRI studies of recognition memory have reported greater hippocampal activity for new compared to old items (e.g., Duzel et al, 2003;Rombouts et al, 2001;.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of hippocampal lesions in humans and fMRI studies generally support the hypothesis of a general role of the hippocampus in relational memory (Spiers et al 2001;Eldridge et al 2005;Fenker et al 2005;Kumaran et al 2007). Right hippocampus activation correlated with novelty detection of both spatial and nonspatial relations of stimulus pairs, but not with novelty detection of single stimuli, which in turn correlated with perirhinal activation (Kohler et al 2005).…”
mentioning
confidence: 75%